Evaluation of producer organisations in the fruit and vegetable sector: Experiences from Hungary and Belgium - Felföldi, J.; Molnár, A.; Gellynck, X. (International Journal of Horticultural Science, 2006)
This paper focuses on the Producer Organisations (POs) in the fruit and vegetable sector in Hungary and in Belgium. Findings are drawn from a survey among members and leaders of POs. The aim of the research is to evaluate the operation of the Hungarian POs and to compare the results with the Flemish ones based on the perception of the respondents. We mark out from the research results that Hungarian PO members and PO leaders’ perception significantly different in the following constructs: satisfaction with the CMO, environmental friendly production and willingness to cooperate. The most important difference between Hungarian and Flemish respondents was about the willingness to cooperate, and about the innovations in trading activities.